Networking strategy for wireless chip area network on PCB - Xuehua LI; Yongbin ZHANG; Yiwen Wang (Dianxin kexue)
According to the special scene of intra/inter chip wireless interconnection system on PCB in WCAN，an efficient networking scheme based on cellular Ad Hoc was proposed，the network model of WCAN-PCB，multiple access，wireless nodes design，routing，and flow control strategy were analyzed. Finally，the network performance comparison with the wireless Mesh scheme was also given. The simulation and computation results show that the proposed scheme could keep a lower network delay and jitter，a higher throughput of network，also maintain a relatively low packet loss rate in the high speed data transmission，primarily serves as a reference value to the future research of WCAN networking architecture and 5G technology.